Harmonic-resonator-based triboelectric nanogenerator as a sustainable power source and a self-powered active vibration sensor - Chen, Jun (Advanced materials (Deerfield Beach, Fla.), 2013)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.